Association of Functional Polymorphisms of KIR3DL1/DS1 With Behçet's Disease - Castaño-Núñez, Ángel; Montes-Cano, Marco-Antonio; García-Lozano, José-Raúl; Ortego-Centeno, Norberto; García-Hernández, Francisco-José; Espinosa, Gerard; Graña-Gil, Genaro; Sánchez-Bursón, Juan; Juliá, María-Rosa; Solans, Roser; Blanco, Ricardo; Barnosi-Marín, Ana-Celia; et al. (Frontiers in Immunology, 2019)
Behçet´s disease (BD) is an immune-mediated vasculitis related to imbalances between the innate and adaptive immune response. Infectious agents or environmental factors may trigger the disease in genetically predisposed individuals. HLA-B51 is the genetic factor stronger associated with the disease, although the bases of this association remain elusive. NK cells have also been implicated in the etiopathogenesis of BD. A family of NK receptors, Killer-cell Immunoglobulin-like Receptor (KIR), with a very complex organization, is very important in the education and control of the NK cells by the union to their ligands, most of them, HLA class I molecules. This study aimed to investigate the contribution of certain KIR functional polymorphisms to the susceptibility to BD. A total of 466 BD patients and 444 healthy individuals were genotyped in HLA class I (A, B and C). The set of KIR genes and the functional variants of KIR3DL1/DS1 and KIR2DS4 were also determined. Frequency of KIR3DL1*004 was lower in patients than in controls (0.15 vs. 0.20, P=0.005, Pc=0.015; OR=0.70; 95%CI 0.54-0.90) in both B51 positive and negative individuals. KIR3DL1*004, which encodes a misfolded protein, is included in a common telomeric haplotype with only one functional KIR gene, KIR3DL2. Both, KIR3DL1 and KIR3DL2 sense pathogen-associated molecular patterns but they have different capacities to eliminate them. The education of the NK cells depending on the HLA, the balance of KIR3DL1/KIR3DL2 licensed NK cells and the different capacities of these receptors to eliminate pathogens could be involved in the etiopathogenesis of BD.